The effect of age of first exposure to competitive fighting on cognitive and other neuropsychiatric symptoms and brain volume. (2nd January 2020) - Bryant, Barry R.; Narapareddy, Bharat R.; Bray, Michael J. C.; Richey, Lisa N.; Krieg, Akshay; Shan, Guogen; Peters, Matthew E.; Bernick, Charles B.
Abstract: It has long been established that fighting sports such as boxing and mixed martial arts can lead to head injury. Prior work from this group on the Professional Fighters Brain Health Study found that exposure to repetitive head impacts is associated with lower brain volumes and decreased processing speed in fighters. Current and previously licensed professional fighters were recruited, divided into active and retired cohorts, and matched with a control group that had no prior experience in sports with likely head trauma. This study examined the relationship between age of first exposure (AFE) to fighting sports and brain structure (MRI regional volume), cognitive performance (CNS Vital Signs, iComet C3), and clinical neuropsychiatric symptoms (PHQ-9, Barratt Impulsiveness Scale). Brain MRI data showed significant correlations between earlier AFE and smaller bilateral hippocampal and posterior corpus callosum volumes for both retired and active fighters. Earlier AFE in active fighters was correlated with decreased processing speed and decreased psychomotor speed. Retired fighters showed a correlation between earlier AFE and higher measures of depression and impulsivity. Overall, the results help to inform clinicians, governing bodies, parents, and athletes of the risks associated with beginning to compete in fighting sports at a young age.